2021
DOI: 10.1111/ppc.12881
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of nursing students violence tendencies on care behaviors

Abstract: Purpose: Although violence is a preventable phenomenon, whose negative effects may be reduced, it should be analyzed with a holistic approach to determine its possible effects on caring behaviors, which constitute the basis of the profession of nursing. This study aims to reveal the reflections of the tendency to violence among the nursing students on their caring behavior. Materials and Methods:A survey was conducted within a convenient sample of 292 nursing students. Personal Informat ion Form, Tendency to V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
(96 reference statements)
0
7
0
1
Order By: Relevance
“…It is possible to develop the care behaviors that form the heart and soul of the nursing profession through education and training processes [70]. When the literature was examined, Karabey et al [55] determined that nursing students' care behaviors were at a high level in their study conducted to refect the violent tendencies of nursing students in their care behaviors. Türk et al [71] reported that students' care behavior scores were high in their study conducted to determine the reasons for choosing a profession and the perception of care behaviors of nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible to develop the care behaviors that form the heart and soul of the nursing profession through education and training processes [70]. When the literature was examined, Karabey et al [55] determined that nursing students' care behaviors were at a high level in their study conducted to refect the violent tendencies of nursing students in their care behaviors. Türk et al [71] reported that students' care behavior scores were high in their study conducted to determine the reasons for choosing a profession and the perception of care behaviors of nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…When the literature is examined, Jeong and Lee [79] reported a positive relationship between verbal abuse experience and emotional coping style in their study to determine the efect of verbal abuse experience, coping style, and resilience on emotional response and stress in nursing students during clinical practice. Karabey et al [55], in their study to determine the refection of nursing students' violence tendencies on care behaviors, found that there was a statistically negative relationship between students' violence tendencies and care behaviors. Again, Labrague and Los Santos [80] and Tabakakis [81] reported that a high level of psychological resilience leads to positive results in the feld of health by increasing the job satisfaction and performance of nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Como observado nas falas, essa situação pode gerar imprudência e negligência no cuidado com os pacientes. A respeito disso, estudos relacionam a violência vivenciada pelos estudantes à oferta de um cuidado pouco humanizado e permeado pela reprodução dos atos violentos (11,12,28,29) .…”
Section: Discussionunclassified
“…Adaptation problems during this period can also impact students' interpersonal relations, academic performance, and health behaviors (Almutairi et al, 2018). Apart from this, university students are especially at risk of adopting negative health behaviors such as unhealthy eating habits, sedentariness, cigarette and alcohol use, substance abuse, suicide attempts, risky driving, unprotected sexual activity, truancy, and home avoidance, and lack of academic interest (Atlam et al, 2017; Karabey et al, 2021). International and national studies have determined that university students generally have poor eating habits (e.g., fast food, low fruit and vegetable intake, and meal skipping) and lower physical activity levels (Bağrıaçık, 2019; Hilger et al, 2017; Lee et al, 2017; Oğuz et al, 2018; Wilson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%